Valorisation of microalga Tetradesmus obliquus grown in brewery wastewater using subcritical water extraction towards zero waste - Ferreira, Alice (2022)
n this study, green technology was applied for extraction of compounds from wastewater-grown microalga biomass with the final goal of obtaining microbiologically safe products within a sustainable biorefinery process with zero waste. Tetradesmus obliquus biomass resulting from brewery wastewater treatment, with (To-CO2) and without CO2 supplementation (To), was submitted to subcritical water extraction (SWE) at temperatures 120-220 degrees C for 10 min. The impact of the different SWE conditions in the obtained liquid extracts and solid residues were investigated for metal content and chemical and microbiological profiles. Gas chromatography-mass spectrometry analysis indicated that of T. obliquus extracts and residues are valuable sources of aliphatic saturated, unsaturated, and alkylated (mostly methylated) hydrocarbons, phenols, esters, and ketones. Polyphenolic content and antioxidant activity were enhanced approximately 4 times by increasing the temperature from 120 to 220 degrees C. Also, the content of polyphenols doubled when T. obliquus was supplemented with CO2 for all the tested temperatures (To: 0.249-1.016 mg GAE mL(-1); To-CO2: 0.437 - 1.767 mg GAE mL(-1)). The microbiological analysis determined that liquid extracts and residues represent safe sources of bioactive components that can be used in different industries. In addition, the lower content of heavy metals in residues suggests the possibility of using the solid waste as animal feed or soil conditioner in agricultural applications.